ANALYSIS OF DETERMINATION THE NUMBER PERSONNEL BASED ON WORKLOAD ACCORDING TO JOB DESCRIPTION (STUDY CASE IN ACCOUNTING INSTITUTIONS) - Ahmadi Ahmadi; Wahyu Endriyanto; Benny Sukandari; Agus Makhrowi (JOURNAL ASRO, 2019)
The workload is highly related to efficient and effective human resource utilization in an organization to achieve organizational objectives, vision, and mission. Various methods are used to optimize the number of personnel in an organization so that each task can be completed quickly and precisely. Accounting Institutions are inseparable from problems regarding the lack of workload with the number of personnel working on it. The change of the Policy gives an impact on the change of Job Description and List of Personnel Arrangements of the organization. To overcome these issues, workload measurement, analysis can be used to determine the optimal amount of personnel required in their working units. This study uses a mental workload measurement so called NASA-TLX and physical workload measurement According to the applicable workload regulation that is in accordance with the Administrative Direction of Workload Analysis. Both methods are then carried out to be compared to each other. The results showed that the physical workload is required in the completion of tasks in each work unit. In addition, the determination of the optimal number of personnel using physical workload or appropriate tasks per task position based Job Description is performed. As a result, it is known that there is an excessive workload in the Sub Service Budget Cost work units with personal shortcomings. On the other hand, there is an excessive personnel number in Administrative Work, Sub Department of Finance Administration and Sub Department Financial Control. The overall conclusion of this study is a need for personnel reduction in a List of Personnel Arrangements currently known as Accounting Institutions to be 39 personnel instead of the existing 48 personnel. Keywords: Workload, NASA-TLX (Task Load Index), assignments Per Task title, Number of Optimal personnel